Impact Of Modifiable Risk Factors On Outcome In Patients With Perforated Peptic Ulcers: A Local Experience - Iqbal, Muhammad; Zia, Muhammad Naeem; Khan, Asma Ali; Chaudhary, Muhammad Salman; Ijaz, Sadaf; Khan, Muhammad Amir (Journal of Rawalpindi Medical College, 2025)
Objective: This study aims to determine the impact of modifiable factors in perforated peptic ulceration on reducing mortality at our local setting of Benazir Bhutto Hospital, Rawalpindi, over two years. Methods: All the patients who were admitted and managed for perforated duodenal ulcer at the emergency department of the Surgical Unit 1 at Benazir Bhutto Hospital, Rawalpindi, from 01-11-2021 to 31-10-2023 were included in the study. The possible causes, co-morbidities, and complications were noted, and data were recorded on a specified proforma. Results: Among thirty-two patients of perforated duodenal ulcers, 63% were smokers, a history of NSAIDs use was present in 37.5% patients, and co-morbidities were present in 25.00% patients. All patients underwent exploratory laparotomy and repair of perforation. The average hospital stay was 5 days, with a range of 1-15 days. The mortality rate in our study was 28.12%. Conclusion: Perforation is still a prevalent complication of peptic ulcer disease. Smoking, increased NSAIDs use, and stressful life play an important role in such cases. Mortality rate is very high in perforated duodenal ulcer cases despite increased understanding of post-operative care.